Do mayors meet the legal requirements of accountability? A look from the electronic portals of municipalities of Santa Catarina (Revista Brasileira de Contabilidade e Gestão, 2014)
The goal of this research is to investigate the capacity of the electronic portals of municipalities of Santa Catarina with population over 10,000 inhabitants to build accountability. This is a descriptive study, conducted through a survey with qualitative and quantitative approach. The observations to verify the accountability in electronic portals took place in October and November 2013. Data collection was performed through the observation protocol based on the analytical model proposed by Raupp (2011), which considers indicators grouped into four categories: zero capacity, low capacity, medium capacity and high capacity. Out of the 122 electronic portals surveyed, 90.16 % had partial disclosure and / or after the deadline of the set of legal requirements on the expenses incurred, showing evidences of no compliance to the legislation. The disclosure, on time, of the set of legal requirements on the expenses incurred, is performed by 9.84 % of the universe studied.
Keywords: accountability; electronic portals; municipalities